Pengaturan Penyalahgunaan Keadaan pada Perjanjian Jual Beli : (Studi Komparatif Antara Hukum Perdata di Indonesia dan Belanda) - Ridho Setiawan Usman; Mutia Cherawaty Thalib; Nurul Fazri Elfikri (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This study examines the regulation of abuse of circumstances in sales agreements through a comparative study between Indonesian and Dutch civil law. Abuse of circumstances is a legal doctrine that protects the weaker party in contracts where there is an imbalance of power and pressure, resulting in a lack of free will from one party. The research aims to understand the concept and analyze the legal consequences in both legal systems. This normative study employs statutory, conceptual, and analytical approaches through literature review and case law analysis. Findings reveal that in Indonesia, abuse of circumstances is not explicitly regulated in the Civil Code and relies on case law and judicial interpretation, whereas in the Netherlands, it is clearly codified in Article 3:44 of the Nieuw Burgerlijk Wetboek (NBW) providing greater legal certainty. The legal consequence in both countries is the annulment of contracts formed under such circumstances and entitlement to compensation for the harmed party. The primary difference lies in codification and consistency of application. This study recommends that Indonesia adopt explicit regulation similar to the Dutch model to enhance legal protection and fairness in sales transactions.